Data Practices in MENA : Case Study - Opportunities and Challenges in Jordan - World Bank (World Bank, Washington, DC, 2021)
Jordan aspires to become a regional digital leader and has identified digital economy as a high priority for the country’s social and economic development. More recently, the Coronavirus disease 2019 (COVID-19) crisis has created an urgency for Jordan to adapt to the post-pandemic world driven by digital infrastructure and services. Against this background, this case study provides an assessment of the data governance practices in Jordan as well as a set of high-level policy recommendations to strengthen data governance in support of a vibrant, safe, and inclusive digital economy. Data governance is a necessary process of managing the availability, usability, integrity, and security of data in public and private systems. Solid data governance ecosystem, supported by capacity building for institutions and inclusive communications and dissemination campaigns, can foster trust in data use in a country and region with a fragile social contract. The diagnostic toolkit used in this report interrogates three pillars: enablers; safeguards; and value creation.